Recurrence of peripheral T-cell lymphoma as granulomas in the lower limbs Granulomas epitelióides cutâneos, como manifestação de recidiva de linfoma de células T periférico - Ana Rita Travassos; João Borges-Costa; João Raposo; Luís Soares Almeida; Paulo Filipe (Sociedade Brasileira de Dermatologia, 2012)
The presence of granulomas in the skin of T-cell lymphoma patients is a rare but well-known phenomenon. The authors present the case of a 44-year-old Caucasian male, with a previously treated peripheral T-cell lymphoma, with cutaneous infiltration and extensive dyschromia on his lower limbs. Skin biopsies revealed the presence of sarcoid granulomas associated with the recurrence of the lymphoma, confirmed by immunostaining and molecular analysis. Although a new scheme of chemotherapy was started, he died 18 months later. There are two different patterns of skin granulomas associated with lymphoma: granulomatous infiltrates admixed with neoplastic cells and cutaneous granulomas constituting a nonspecific manifestation of the underlying lymphoma, but presently there is no evidence supporting their relationship with lymphoma prognosis. A presença de granulomas cutâneos associados a linfomas é um fenômeno raro, mas bem conhecido. Um homem, 44 anos de idade, com diagnóstico prévio de linfoma de células T periférico, foi enviado à nossa consulta por infiltração cutânea e extensa discromia nos membros inferiores. A biopsia cutânea revelou a presença de granulomas epitelioides associados à recidiva do linfoma, confirmada pela marcação imuno-histoquímica e estudo molecular. Apesar de iniciado novo esquema de quimioterapia, o doente faleceu 18 meses depois. Na literatura são descritos dois tipos de granulomas cutâneos na presença de linfomas: associados à infiltração cutânea pelo linfoma ou como uma manifestação não específica do linfoma. Contudo, atualmente não há evidência que suporte a sua relação com o prognóstico dos linfomas.